The missing magic - Elliott, Rebecca (2022)
Unicorn Bo and friends attend the Big Festival of Magic hoping to show off their magical skills, but when all the magic goes missing they must find a way to find and return the magic.
Festival week -- Use your magic! -- What's going on?! -- Gnome that knows -- Hobgoblin -- Magic returns -- Magical day.
Accelerated Reader
Keywords: Unicorns -- Juvenile fiction; Magic -- Juvenile fiction; Lost articles -- Juvenile fiction; Diaries -- Juvenile fiction; Unicorns -- Fiction; Magic -- Fiction; Lost and found possessions -- Fiction; Diaries -- Fiction; JUVENILE FICTION -- Reader -- Chapter Books; JUVENILE FICTION -- Animals -- Dragons, Unicorns & Mythical; JUVENILE FICTION -- Comics & Graphic Novels -- Fantasy; Diaries; Lost articles; Magic; Unicorns; Unicorns -- Juvenile fiction; Magic -- Juvenile fiction; Lost and found possessions; Diaries -- Juvenile fiction; Unicorns -- Fiction; Magic -- Fiction; Lost and found possessions -- Fiction; Diaries -- Fiction; Diary fiction; Children's stories; Juvenile works; Fiction; Fantasy fiction; Diary fiction; Fantasy fiction; Fantasy fiction; Diary fiction; Journaux intimes fictifs